2018
DOI: 10.32528/ellite.v3i1.1776
|View full text |Cite
|
Sign up to set email alerts
|

Interactive Multimedia in Teaching Reading

Abstract: This research is intended to investigate the effectiveness of interactive multimedia for teaching reading in junior high school. Based on my preliminary research, there were many problems in teaching and learning reading for junior high school students. Seeing those problems, the researcher tried to implement the interactive multimedia in teaching reading. Then, the method used in this research is quasi experimental with test as the instrument for collecting the data. The students' score was analyzed using SPS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 2 publications
0
7
0
Order By: Relevance
“…Previous study on the use of interactive multimedia in learning was conducted by (Sari, 2018 ;Elviana, 2020) showed a significant increase in learning outcomes. In line with Sari and Elviana, study conducted by (Wahyuni, 2016) showed that the interactive multimedia is included in the feasible criteria.…”
Section: Instructional Games Modelmentioning
confidence: 98%
See 1 more Smart Citation
“…Previous study on the use of interactive multimedia in learning was conducted by (Sari, 2018 ;Elviana, 2020) showed a significant increase in learning outcomes. In line with Sari and Elviana, study conducted by (Wahyuni, 2016) showed that the interactive multimedia is included in the feasible criteria.…”
Section: Instructional Games Modelmentioning
confidence: 98%
“…Learning media is one of components in the lesson that has an important role in teaching and learning activities. The use of learning media in the teaching learning process can generate the new interest and desires, motivation and stimulation of learning activities, and even bring psychological effects on students, so that it will help the effectiveness of the learning process in delivering messages and lesson content at that time (Sari, 2018). In addition to arouse students' motivation and interest, learning media can also help students to improve the understanding and to present the data in an interesting and condensed way (Surasmi, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Students' fluency and speaking skills can show their competence in learning English [7]. Successful communication involves the use of speaking skills to deliver opinions and questions [8]. Furthermore, being able to communicate effectively is one of the essential hallmarks of the global society of the 21st century.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Digital teaching materials can display some material using interactive learning media (Sugianto et al, 2013). Sari (2018) found that interactive multimedia effectively taught reading, significantly improving the students' interest and reading skills. Multimedia can address cognitive skills: focusing, information gathering, memorizing, organizing, analyzing, generating, and evaluating (Ampa et al, 2013;Ivers & Baron, 2010).…”
Section: The Need For Interactive Multimediamentioning
confidence: 99%